Enzyme kinetics (Michaelis-Menten) - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Initial reaction velocity, Catalysed vs. uncatalysed reaction pathways, Enzyme saturation/Maximum reaction velocity, Michaelis-Menten equation, Energy barriers and rate constants, Measuring Km and Vmax, The Lineweaver-Burk plot
Reviewed at 2022/11/27